Use of Nonsteroidal Anti‐Inflammatory Drugs for Symptomatic Treatment of Episodic Headache. Issue 3 (21st May 2016) - Affaitati, Giannapia; Martelletti, Paolo; Lopopolo, Mariangela; Tana, Claudio; Massimini, Francesca; Cipollone, Francesco; Lapenna, Domenico; Giamberardino, Maria Adele; Costantini, Raffaele
Abstract: Introduction: Primary headaches have high epidemiologic impact but their symptomatic treatment often remains problematic. Nonsteroidal anti‐inflammatory drugs (NSAIDs) are frequently used, but their modality of employment and efficacy/differential efficacy are highly variable. This study investigated current NSAID use for episodic headache at an Italian headache center (January 2000 to February 2013). Methods: A retrospective evaluation was performed on 6, 443 patient records: migraine ( n = 2, 330), tension‐type headache (TTH; n = 807), and migraine plus TTH ( n = 3, 306). Results: Among migraine patients, 80% had used NSAIDs in the past year. Preferences were: nimesulide (57%), ketoprofen (25%), and ibuprofen (24%); complete efficacy was significantly higher than incomplete/absent efficacy ( P < 0.0001). NSAIDs were replaced with triptans in 53% of patients at first visit; after 1 year there was a spontaneous significant return to NSAIDs (56%; P < 0.0005). Among TTH patients, 90% were NSAID users; preferences were: nimesulide (48%), ketoprofen (47%), and diclofenac (19%), with significantly higher complete vs. incomplete/absent efficacy (nimesulide and ketoprofen, P < 0.02). Replacement with analgesics was performed in 24% of patients; after 1 year, there was a 29% return to NSAIDs. Among migraine plus TTH patients, 89% were NSAID users. Preferences were: nimesulide (44%), ibuprofen (42%), and ketoprofen (38%), with significantly higher complete vs. incomplete/absent efficacy (0.001 < P < 0.0001). Replacement with analgesics was performed in 31% of patients; after 1 year, there was a 37% return to NSAIDs. Conclusions: Nonsteroidal anti‐inflammatory drug use in headache was higher than could be hypothesized based on guidelines, with NSAID preferences not entirely coinciding with international recommendations. This outcome suggests the need for greater awareness of all treatment options in headache by both patients and physicians.